HUBUNGAN PENGETAHUAN MENGENAI PATOFISIOLOGI COVID-19 DAN SIKAP TERHADAP PERILAKU PENGGUNAAN MASKER KAIN SEBAGAI UPAYA PENCEGAHAN COVID-19 PADA MAHASISWA FAKULTAS KEDOKTERAN UPN VETERAN JAKARTA ANGKATAN 2017 - Maria Yosefhine (2020)
Coronavirus Disease (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). COVID-19 can be prevented by knowing about pathophysiology of COVID-19, so that it is expected to form a positive attitude toward wearing cloth masks. The purpose of this study is to determine the relationship between knowledge about the pathophysiology of COVID-19 and students' attitudes towards the behaviour of using cloth masks as a prevention of COVID-19 on final year students of Fakultas Kedokteran UPN Veteran Jakarta. This research was observational analytical research cross sectional with the consecutive sampling. The data were collected by online questionnaire. The total sample of 75 students showed that 70 students (93.3%) had good knowledge of the pathophysiology of COVID-19, 65 students (86.7%) had a positive attitude, and 68 students (90.7%) had the well behaviour of using cloth masks. The bivariate analysis with Fisher's Exact Test showed were relationship between knowledge of the pathophysiology of COVID-19 (p=0,000) and students' attitudes (p=0.046) towards the behaviour of using cloth masks as a prevention of COVID-19 on final year students of Fakultas Kedokteran UPN Veteran Jakarta. The knowledge about the pathophysiology of COVID-19 that the SARS-CoV-2 infected human airway through the bonding of virus protein with the ACE-2 (Angiotensin Converting Enzyme-2) receptor in lung cells, could encourage students' positive attitude of using cloth mask whenever go outside as a prevention of COVID-19.